f-4=6/2f+6

Simple and best practice solution for f-4=6/2f+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f-4=6/2f+6 equation:



f-4=6/2f+6
We move all terms to the left:
f-4-(6/2f+6)=0
Domain of the equation: 2f+6)!=0
f∈R
We get rid of parentheses
f-6/2f-6-4=0
We multiply all the terms by the denominator
f*2f-6*2f-4*2f-6=0
Wy multiply elements
2f^2-12f-8f-6=0
We add all the numbers together, and all the variables
2f^2-20f-6=0
a = 2; b = -20; c = -6;
Δ = b2-4ac
Δ = -202-4·2·(-6)
Δ = 448
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$f_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$f_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{448}=\sqrt{64*7}=\sqrt{64}*\sqrt{7}=8\sqrt{7}$
$f_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-20)-8\sqrt{7}}{2*2}=\frac{20-8\sqrt{7}}{4} $
$f_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-20)+8\sqrt{7}}{2*2}=\frac{20+8\sqrt{7}}{4} $

See similar equations:

| r+17/16=3 | | m/3+7=0 | | 7+3c=11=4c-7+8c | | p+(-2)=-6 | | -4u=6u-10 | | -u+100=214 | | 14=-7(8x+3) | | 8(1+3v)=104 | | 8x-4+4x=-16 | | 4(b+1)-5-3b+2=18 | | 9r-9=90 | | y=-4^2+7 | | 3x+4x+2=6x+2+x | | 14(5n-9)-3(2n+1)=17n | | 10=a*(2-(-4))^2+5 | | 8x+6x+2=-12 | | 2y-4=32 | | 5-8u=-8u-1 | | -12+7x=5x-6 | | 1-7x-3x=-9 | | 600+0.03x=2400 | | 2y-5=32 | | 10.50p+14=15(p-5) | | -5(v+3)+2v+7=8v+9 | | 3(x-2)+11=5(x-3)+5 | | y=4^2+10 | | m+(m-)=7 | | v/7-5=-3 | | 14x-3+(-4x)=5x+17 | | y=1/5-5-9 | | 5(X+3)=18x+2 | | 6y+15=5y+21 |

Equations solver categories